Blood-feeding adaptations and virome assessment of the poultry red mite Dermanyssus gallinae guided by RNA-seq - Ribeiro, José M. (2023)
Dermanyssus gallinae is a blood-feeding mite that parasitises wild birds and farmed poultry. Its remarkably swift processing of blood, together with the capacity to blood-feed during most developmental stages, makes this mite a highly debilitating pest. To identify specific adaptations to digestion of a haemoglobin-rich diet, we constructed and compared transcriptomes from starved and blood-fed stages of the parasite and identified midgut-enriched transcripts. We noted that midgut transcripts encoding cysteine proteases were upregulated with a blood meal. Mapping the full proteolytic apparatus, we noted a reduction in the suite of cysteine proteases, missing homologues for Cathepsin B and C.